The politics of repressed guilt : the tragedy of Austrian silence - Leeb, Claudia (Edinburgh University Press, 2018)
Drawing on the work of Hannah Arendt and Theodor W. Adorno, Claudia Leeb discusses guilt and democracy in the case of Austrian Nazi perpetrators and recent public controversies surrounding Austria's involvement in the Nazi atrocities. She shows us that only by guilt can individuals and nations take responsibility for their past crimes.